2021
DOI: 10.1002/adhm.202100978
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Metabolism Targeted Nanoplatform for Efficient Triple‐Negative Breast Cancer Combination Therapy

Abstract: Tumor reprogram pathway of mitochondrial metabolism is an emerging approach for malignant tumor treatment, such as triple-negative breast cancer. In this study, a tumor/mitochondria cascaded targeting, adenosine-triphosphate (ATP) responsive nanocarrier of zeolitic imidazolate framework-90 (ZIF-90) for breast cancer combination therapy is reported. Atovaquone (AVO) and hemin are loaded into ZIF-90, then a peptide iRGD with tumor-targeting ability is modified on the ZIF-90 nanoplatform. Hemin can specifically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Recent studies identified novel functional roles of BACH1 in the regulation of metabolic pathways in cancer cells through transcriptional suppression of mitochondrial membrane genes. As a transcriptional factor, BACH1 supports aerobic glycolysis in breast cancer cells by increasing the expression of metabolic enzymes involved such as hexokinase 2 (HK2), lactate dehydrogenase A and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) 9 , 10 . Additionally, BACH1 promotes cancer cells metastasis by directly promoting the expression of E-cadherin, other epithelial-mesenchymal transition-related proteins and matrix metalloproteinases (MMPs), and suppressing the expression of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified novel functional roles of BACH1 in the regulation of metabolic pathways in cancer cells through transcriptional suppression of mitochondrial membrane genes. As a transcriptional factor, BACH1 supports aerobic glycolysis in breast cancer cells by increasing the expression of metabolic enzymes involved such as hexokinase 2 (HK2), lactate dehydrogenase A and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) 9 , 10 . Additionally, BACH1 promotes cancer cells metastasis by directly promoting the expression of E-cadherin, other epithelial-mesenchymal transition-related proteins and matrix metalloproteinases (MMPs), and suppressing the expression of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the positive charges, ZIF-90 can actively target mitochondria. More importantly, ZIF-90 can be disassembled by mitochondrial ATP to liberate the loaded drugs because of the competitive coordination between ATP and Zn 2+ ( Lu et al, 2021 ). Secondly, they chose both 2-Methoxyestradiol (2-ME) and thioketal-linked camptothecin (TK-CPT, a prodrug) as the drugs.…”
Section: Mitochondria Targeting With the Aid Of Multifunctional Nanosystemsmentioning
confidence: 99%
“…29,30 Zeolitic imidazole framework-90 (ZIF-90), consisting of imidazole-2-carboxaldehyde (2-ICA) and Zn 2+ , is widely studied in biomedical applications for its biocompatibility, and the properties of ATP/pH-responsive decomposition. [31][32][33][34] Especially, the aldehyde group of ZIF-90 provides a facile functional position for post-modification. For example, doxorubicin (DOX) can be covalently bound to ZIF-90.…”
Section: Introductionmentioning
confidence: 99%